The Global Surge in Type 2 Diabetes Mellitus Among Young Adults: Causes, Habits, and Public Awareness through a Literature Review Study - Rosa Adelina; Jenisha Rani Fajra; Zulaila Hunafa; Rawwdha Luthfi Nur Muhamad; Rangga Dwi Kurniadi; Siti Naila Nafisya (Mimbar Agama dan Budaya, 2023)
The prevalence of type 2 diabetes mellitus has doubled globally in the past 40 years, including young adults. This phenomenon was caused by habits, particularly their preferences for snacks and SSBs. Other factors were accessibility, social media influence, and lifestyle changes contributing to the increased consumption of high-sugar foods and drinks. This study was a literature review study. The result of this study is that the lack of public awareness in choosing suitable and halal food was identified as a significant contributor to the high prevalence of diabetes in Indonesia. In addition, it is essential to enhance public knowledge and prevent the escalating diabetes prevalence.